2022
DOI: 10.3390/app12105138
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid ANN-GA Model for an Automated Rapid Vulnerability Assessment of Existing RC Buildings

Abstract: Determining the risk priorities for the building stock in highly seismic-prone regions and making the final decisions about the buildings is one of the essential precautionary measures that needs to be taken before the earthquake. This study aims to develop an Artificial Neural Network (ANN)-based model to predict risk priorities for reinforced-concrete (RC) buildings that constitute a large part of the existing building stock. For this purpose, the network parameters in the network structure have been optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 89 publications
0
12
0
3
Order By: Relevance
“…Many studies [39][40][41][42][43][44] have shown that, D and C could be assumed to follow the lognormal distributions when analyzing their seismic fragility. Therefore, freeze-thaw cycles could be introduced as a variable to build a new seismic fragility function, as shown in Equation ( 16).…”
Section: Seismic Fragility Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies [39][40][41][42][43][44] have shown that, D and C could be assumed to follow the lognormal distributions when analyzing their seismic fragility. Therefore, freeze-thaw cycles could be introduced as a variable to build a new seismic fragility function, as shown in Equation ( 16).…”
Section: Seismic Fragility Theorymentioning
confidence: 99%
“…OpenSEES [38][39][40]42,43] is an efficient nonlinear seismic analysis software, which has the advanced modeling capabilities and contains many material models, elements and algorithms for the seismic assessments of RC structures. Therefore, OpenSEES was utilized to construct the nonlinear FE model of the bridge.…”
Section: Bridge Description and Fe Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower building area, especially on the ground storey, is replaced by larger building areas on the upper storeys. Heavy overhang status is clearly stated within the negativity parameters taken into account in the rapid assessment method [33], [34], [35], [36]. In this method, the presence of heavy overhangs is determined according to Figure 3.…”
Section: Heavy Overhang In Rc Structuresmentioning
confidence: 99%
“…Li et al used remote sensing data before and after the earthquake through the decision tree method, in which the damaged buildings were divided into four grades [2]. The neural network of the genetic algorithm (GA) and the neural network composed of multi-layer perceptron (MLP) are used to predict the risk level of damage to reinforced-concrete (RC) structures [3,4]. The method achieves detailed investigation and inspection of buildings before the earthquake, reducing the loss of life and property.…”
Section: Introductionmentioning
confidence: 99%